2018
DOI: 10.1111/imj.13650
|View full text |Cite
|
Sign up to set email alerts
|

Neurological presentations revealing acquired copper deficiency: diagnosis features, aetiologies and evolution in seven patients

Abstract: Progressive PCS with anaemia and lymphopenia must raise the possibility of an ACD. Early copper supplementation could increase the neurological prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Performance of the radiocopper test was comparable to 24‐hours urinary copper excretion and much better than those of serum ceruloplasmin and total copper. Although the diagnostic value of 24‐hours urinary copper output was high in our study, perturbed copper excretion may be observed in other circumstances (eg, because of liver failure of any origin or chronic zinc intake) and problems with urine collection can cause difficulties in diagnosis . Interestingly, we also confirmed the low diagnostic value of NCC, which is not recommended as a diagnostic tool .…”
Section: Discussionsupporting
confidence: 45%
“…Performance of the radiocopper test was comparable to 24‐hours urinary copper excretion and much better than those of serum ceruloplasmin and total copper. Although the diagnostic value of 24‐hours urinary copper output was high in our study, perturbed copper excretion may be observed in other circumstances (eg, because of liver failure of any origin or chronic zinc intake) and problems with urine collection can cause difficulties in diagnosis . Interestingly, we also confirmed the low diagnostic value of NCC, which is not recommended as a diagnostic tool .…”
Section: Discussionsupporting
confidence: 45%
“…A new deficiency in copper was seen in one study; a deficiency of such micronutrients may cause peripheral neuropathy 40 and indirectly contribute to OI. However, copper deficiency is known to cause myelopathy more than peripheral neuropathy 41 . In the included studies, pathophysiological changes after BS were not favouring inducing OI except for the study of meal volume and posture, 31 which might reflect a dumping syndrome phenomenon 42 …”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic vacuolization within erythroid and myeloid precursors are unique to copper deficiency, and can help distinguish between these two conditions 72 . Neurologic involvement often takes the form of progressive spastic‐ataxic gait due to myelopathy which is very similar to subacute combined degeneration 73,74 . Other neurologic features include myeloneuropathy, optic neuropathy, and motor neuron disease.…”
Section: Disorders Of White Blood Cellsmentioning
confidence: 99%